A novel sampling strategy for surveying high-worth individuals: An application using the socio-economic panel - Carsten Schröder; Charlotte Bartels; Martin Kroh; Markus Grabka; Rainer Siegers (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
High-worth individuals are typically underrepresented or completely missing in population surveys. The lack of a register-based sampling frame on high-worth individuals in many countries challenged previous attempts to sample high-worth individuals in voluntary scientific surveys. In a novel research design, we draw on register data on the shareholding structures of companies as a sampling frame. Our design builds on the empirical regularity that high-worth individuals are likely to hold at least part of their assets in the form of shareholdings. Based on data from over 270 million companies worldwide, we identified individuals who are both German residents and registered shareholders of companies. In a feasibility study, we interviewed 124 households from a gross sample of 2,000 anchor persons. Our analysis shows that register data on shareholding structures correctly identifies the individuals' rank in the wealth distribution, that the quality of personal information, particularly the residential address, is efficiently high for subsequent interviewing, and that the approach can fill a major data and research gap in the study of high-worth individuals and the top-end of the wealth distribution.
Keywords: C83; D31; 330